Reinforcing the Hydrosocial Cycle to foster water governance and stakeholders’ interdependence in urban agroecosystems: a local test in Benidorm, Spain - Ricart, Sandra; Villar, Rubén; Hernández-Hernández, María; Rico-Amorós, Antonio M.; Olcina-Cantos, Jorge; Baños, Carlos (Frontiers in Agronomy, 2023)
The Hydrosocial Cycle (HSC) has been widely applied and discussed as a consolidated research line to rethink the contemporary challenges that condition the urban and agroecosystem nexus. However, additional research directions are still open to guide policy and decision-makers in reinforcing stakeholders’ engagement and interaction to resolve tensions between water demands. This perspective paper suggests updating the HSC approach to improve the analysis of stakeholder interaction when addressing water scarcity in waterscapes. After briefly review the most relevant contributions of the HSC approach in the last two decades, we develop a preliminary framework to reinforce stakeholders’ interdependence analysis by designing a questionnaire to synthesize five main behavioral patterns conditioning stakeholders’ interactions: relevance, representativeness, recognition, assessment, and collaboration. Then, each pattern is organized in a triple-loop approach: to be, to do, and to share to characterize the mutual (mis)understanding of the stakeholders. The results of its application to Benidorm (south of Spain), a mass-tourism destination coexisting with rural development in tension for water supply, exemplified how 1) most stakeholders consider themselves important, but some of them are unaware of the role of others, 2) all stakeholders receive a higher punctuation in terms of functions rather than actions, and 3) all stakeholders agree on the benefits of the predisposition of parties (willingness) to achieve agreements in the short or medium term. Future research should consider how to address the lack of representativeness and power imbalance together with mechanisms to reinforce longitudinal studies in which actions from stakeholders could be contrasted.